Karyotypic comparison of acacia mangium willd., A. auriculiformis A. cunn. Ex benth and their F1 and F 2, hybrids - Ab Shukor, Nor Aini; Abd Rashid, M.; Itam, K. (Sauerlander, 1994)

(untitled)
Cytological data for Acacia mangium WILLD., A. auriculiformis A. Conn. Ex BENTH and their F, and F2 hybrids are presented. Somatic chromosome number of there species confirmed that they have 2n=2x=26. Average absolute chromosome length ranged from 1.210 um I 0.0010 (um in A. auriculiformis to 2.467 Aum i 0.0278 pm in A. mangium, with hybrids F1 and F2 producing intermediate values. These karyotypes are unique and species specific.